The Relationship of Hedonic Lifestyle with Consumptive Behavior in E-Commerce Users Adolescent - Aini, Dea Fitri; Widiastuti, Netty; Widyana, Rahma; Aziza, Maghfira Nur; Wedadjati, Ratna Sesotya (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to determine the relationship between hedonic lifestyle and consumptive behavior in adolescent e-commerce users. This study proposes a hypothesis that there is a positive relationship between hedonic lifestyle and consumptive behavior in adolescent e-commerce users. The subjects in this study were 116 adolescents with an age range of 17-22 years. The data collection method used in this study is to use the Consumptive Behavior Scale and the Hedonic Lifestyle Scale. The data analysis technique used is using product moment correlation. Based on the results of data analysis, the correlation coefficient (rxy) = 0.800 with p = 0.000 (p < 0.001) shows that the hypothesis proposed in this study is accepted, namely there is a positive correlation between hedonic lifestyle and consumptive behavior in adolescent e-commerce users. The coefficient of determination (R2) is 0.639 so it can be said that the hedonic lifestyle contributes 63.9% to consumptive behavior and the remaining 36.1% is influenced by other factors.